The perception of the psychoeducational effects of the dominican female migration on their children left behind - de D. Uriarte, Juan (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
Unlike in the past, today many women from LatinAmerica and the Caribbean decide to emigrate alone and are separated from their children for several years. Using a two-stage Delphi technique with a group of 73 key informants, the objective of the research was to discover the perception in Dominican society of the psychoeducational consequences for children of the emigration of their mothers. 62 variables were gathered and these were divided into five categories: school, home, peers, personality and others, 20 of which obtained the greatest consensus amongst the informants. In short, the most signifi cant consequences for children are those associated with poor school performance, aggressiveness, depression and isolation, and are independent of sex or age differences, in short, a negative social perception.
Keywords: Migratory separation; Maternal absence; Social perception; Children of emigrants